Halal Tourism and Destination Identity: A Conceptual Discussion on the Integration of Islamic Values in Tourism Branding - Riki Maulana (Islamicate Institute, 2026)
This conceptual paper explores how Islamic values can be integrated into destination branding to shape a distinct halal tourism identity. While halal tourism has grown as a global phenomenon, especially in Muslim majority countries such as Indonesia, its conceptual foundations remain fragmented. This article argues that halal tourism branding should move beyond functional aspects (e.g., halal certification, facilities) toward embedding Islamic values such as trust (amanah), honesty (ṣidq), and hospitality (ḍiyāfah) into the core of destination identity. Drawing from destination branding theory, consumer trust models, and Islamic value frameworks, this paper develops a conceptual lens for understanding how spiritual, ethical, and cultural dimensions co create a destination’s halal identity. The study contributes to the theoretical enrichment of halal tourism research and offers insights for policymakers, destination marketers, and tourism practitioners in Muslim contexts.